THREE DIMENSIONAL BATHYMETRIC MODELING TO DETERMINE THE FOOT OF CONTINENTAL SLOPE - Guruh Pratomo (NIM 25105012), Danar
ABSTRACT: The foot of continental slope is a reference that used in criteria to determine the outer limits of continental shelf, where the shelf extends beyond 200 nautical miles from baseline. The location of the foot of continental slope determined with calculating the maximum change of gradient at the base of the continental slope from depth profiles. Maximum interval among depth profiles is 60 nautical miles. In this research, depth profile which use to determine the foot of continental slope was derived from the three dimensional bathymetric model that developed with gridding approach. The grid value of the three dimensional bathymetric model obtained with interpolation from Bathymetric data of DMRM 1996-1998 project. There is three interpolation methods used in this research: [1] triangulation with linier interpolation, [2] inverse distance weighting and [3] kriging. In this research, three dimensional bathymetric model with kriging interpolation is the optimum model to determine the foot of continental slope when reviewed from the quality of model and the position of the foot of continental slope which resulted.